2018–2019 Florida Citrus Production Guide: Interpreting PPE Statements on Pesticide Labels - Frederick M. Fishel (EDIS)
This 3-page fact sheet is part of the 2018–2019 Florida Citrus Production Guide. It is meant to help readers understand the revised PPE statements now part of labels on pesticide products used on farms, forests, nurseries, and greenhouses. Written by Frederick M. Fishel and published by the Agronomy Department, January 2019.